Developing General and Subject Competences of Primary School Pupils in the Context of Integrated Education: the Case of one Lithuanian School - Ponomariovienė, Jovita; Jakavonytė-Staškuvienė, Daiva (Journal of Education Culture and Society, 2022)
Aim. The aim of the research is to provide a scientific justification for the integrated development of general and subject-specific competences of primary school pupils.Methods. The exploratory qualitative case study was conducted in a private school in Lithuania. The integrated activities covered the content of Lithuanian language and science education, as well as general competences such as communication and digital competences. The activity was implemented in grade 4 with 12 pupils (8 boys and 4 girls). A semi-structured interview with the class teacher was also conducted.Results and conclusion. The data from the empirical study were analysed according to the following thematic clusters: interest in the activity, group work, searching for information in the encyclopaedia and in electronic sources, working with a robot when integrating the digital skills and the content of science education, descriptions of animals as a summarising and consolidating activity. The study found that if the educational process is well thought out, if the pupils are interested, they can work independently and support each other in explaining the content, while the teacher becomes an observer, a facilitator, and can concentrate on the pupils’ individual activities during this process. Well-designed tasks with the robot develop not only digital literacy skills, but also the reinforcement of subject content related to the use of concepts.Originality. The case study provides valuable insights into the implementation of an educational process that integrates general and subject-specific competences, and the detailed description of the activities shows which tasks support students’ independent learning.